A Case for computerising syntactic transformations in augmenting communication development - Purushothama G (Journal of All India Institute of Speech and Hearing, 1970)
Augmenting speech communication by providing alternate means even in Us most sophisticated forms is cumbersome mainly compared to oral output. The mechanisms of augmenting mainly provide for the form of expression which are fixed and generally less generative. To that extent it becomes difficult for thelanguage delayed children to express their intent in appropriate syntactic forms. It is proposed that automatising the transformation would make it easy for delayed children to express.